Angiotensin II status and sympathetic activation among hypertensive patients in Uganda: a cross-sectional study. (December 2015) - Mayito, Jonathan; Mungoma, Michael; Kakande, Barbara; Okello, Dove; Wanzira, Humphrey; Kayima, James; Mondo, Charles
Abstract Background Sympathetic activation and renin-angiotensin system are essential for development and sustenance of hypertension. However, the status of these systems has not been well evaluated among patients in an African setting. This study therefore set out to assess the angiotensin II status and sympathetic activation among hypertensive patients in Uganda. Methods In this cross sectional study conducted at Mulago, the national referral hospital, blood samples were taken to measure angiotensin II, metanephrines and normetanephrines. Urine samples were also taken for measuring urine creatinine and sodium. The angiotensin II categories were defined using the Mosby's Diagnostic and Laboratory Test References. 9th ed while the metanephrines and normetanephrine categories were defined using the Makerere University Biosafety II Immunology Laboratory reference values. Results 162 patients were consented and enrolled into the study, of these 136 (84 %) had low, 15 (9 %) had normal, while, 11 (7 %) had high angiotensin II levels. 142 (88 %) participants had normal levels of metanephrine, while 20 (12 %) had high levels. Only 88 were assessed for metanephrines and of these 85 (97 %) had normal, while 3 (3 %) had raised levels. Urine sodium was associated with low and normal angiotensin II levels (P value 0.007). Female gender and diastolic blood pressure were associated with a protective effect against high normetanephrines (OR 0.29, P value 0.015), 80–89 mmHg (OR 0.19, p value 0.053), above 100 mmHg (OR 0.27, p value 0.022). Current smoking status was associated with high risk for abnormal normetanephrines (OR 17.6, P value −0.022) while former smoking was associated with high risk for abnormal metanephrines (OR 18.7, p value 0.022). After multivariate analysis, all the significant variables at bivariate analysis were still significant except those who stopped smoking and those with a BP at 80–89 which were not significant. Conclusions Hypertensive patients in this setting have predominantly low angiotensin II hypertension as a result of high salt intake. Sympathetic activation is not a significant mechanism of hypertension in this study population, more so in the females, with the exception of smokers who have a highly activated sympathetic system. Therefore, the use of agents targeting renin angiotensin and sympathetic systems as single first line antihypertensive agents in this setting should be re-evaluated if such patients are to be treated effectively.